Television viewing academic performance and participation in non academic activities among adolescents school children in the educational division, Maharagama - Thenuwara, N.V.J (My University, 2008)
Adolescents all over the world have been facing "mass media explosion" during past twenty years. Television has been found to be the most popular media among this age group. Pattern of television viewing among adolescents and its association on academic and non-academic activities may vary from country to country. This cross sectional study aimed to assess the VleWlt1g pattern of television/CD/DVD, factors related to patternof viewing and association between academic performance, Participation in non academic activities and pattern of viewing television CD/DVD, among adolescent school children in the educational division, Maharagama.Stratified cluster sampling with probability proportionate to sample size method was used to select the study population and a self-administered questionnaire was the study instrument. A total of 615 students were included in the study. A great majority of students (98.7 percent ) were 12 years old and two third were boys. Nearly 60 percent of mothers and 75 percent percent of fathers of the study population had passed G.C.E.O/L or above. A majority of mothers were housewives and fathers were clerks or technicians while 57 percent reported a monthly income of less than 20,0001